2010
DOI: 10.1039/b9nj00745h
|View full text |Cite
|
Sign up to set email alerts
|

The extended time evolution size decrease of gold nanoparticles formed by the Turkevich method

Abstract: Gold nanoparticle (Au NP) solutions were synthesised by the Turkevich reduction method and stored in either the light or dark. All solutions were monitored daily using UV-visible absorption spectroscopy and displayed surface plasmon resonance (SPR), typical of Au nanoparticle colloids. An increase in SPR intensity, a narrowing of the SPR peak as well as a gradual shift towards lower wavenumbers over time indicated a decrease in average nanoparticle diameter and a more mono-dispersed particle size. After two we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
2
35
0
2
Order By: Relevance
“…Figure 4a presents chromatograms obtained for the freshly prepared Au/Pd core/shell NPs and those that had undergone thermal treatment for 4 and 12 h (sample B, fabricated as described in the ''Experimental'' section). Upon increasing the storage time, the intensity of the signal for the Au/Pd core/shell NPs decreased, the peak width broadened slightly, and the retention time decreased, presumably as a result of Ostwald-type growth (aggregation) [27] that increased the sizes of the Au/Pd core/shell NPs during thermal treatment. The results are consistent with those from a previous study reported by Cha et al [30], who revealed a more-rapid growth rate for Pd NPs upon increasing the temperature.…”
Section: Separation Of Np Standards Using Secmentioning
confidence: 95%
See 1 more Smart Citation
“…Figure 4a presents chromatograms obtained for the freshly prepared Au/Pd core/shell NPs and those that had undergone thermal treatment for 4 and 12 h (sample B, fabricated as described in the ''Experimental'' section). Upon increasing the storage time, the intensity of the signal for the Au/Pd core/shell NPs decreased, the peak width broadened slightly, and the retention time decreased, presumably as a result of Ostwald-type growth (aggregation) [27] that increased the sizes of the Au/Pd core/shell NPs during thermal treatment. The results are consistent with those from a previous study reported by Cha et al [30], who revealed a more-rapid growth rate for Pd NPs upon increasing the temperature.…”
Section: Separation Of Np Standards Using Secmentioning
confidence: 95%
“…Figure 3a displays chromatograms obtained from the freshly prepared and 4-and 12-h thermally treated Au NPs (sample A, fabricated as described in the ''Experimental'' section). The intensity of the signal for the Au NPs decreased and the retention time elongated slightly upon increasing the heating time-presumably as a result of ripening digesting, which decreases the size of Au NPs [27].…”
Section: Separation Of Np Standards Using Secmentioning
confidence: 98%
“…4−6,9,13−17 Most often, it leads to spherical NPs, but not always. 18 Essentially, DR is a thermochemical step that follows the SMAD, 4,5 the Turkevich 3 or the reverse micelle synthesis 11,19,20 in which a ligandexchange reaction induces the redistribution of atoms from polydisperse NPs and leads to a much narrower size distribution; typically with smaller average size, although the opposite has also been observed. 6,21 The term DR introduced by Klablunde and co-workers 10 is often associated with heating the as-prepared, polydisperse colloidal solution in the presence of excess strong capping ligand at or near the boiling point of the solvent under reflux.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this case, the solution was usually stored in the dark at room temperature for several days before use. This was reported to have a beneficial effect on the AuNP quality, [104] although it was not found here.…”
Section: Analysis Of Citrate Aunps Via Optical Spectroscopymentioning
confidence: 76%